Optimization of a wet microalgal lipid extraction procedure for improved lipid recovery for biofuel and bioproduct production. (October 2015) - Sathish, Ashik; Marlar, Tyler; Sims, Ronald C.
Highlights: Modified wet lipid extraction procedure extracts 77% of transesterifiable lipids. Lipids isolated account for 72% of transesterifiable lipids in the algae biomass. Side streams can be used as bioproducts or as feedstock for bioproduct production. Solid precipitate phase formed contains 11.2 wt% nitrogen (70% protein by mass). LEA biomass has higher C/N ratio after procedure and aqueous phase rich in nutrients. Abstract: Methods to convert microalgal biomass to bio based fuels and chemicals are limited by several processing and economic hurdles. Research conducted in this study modified/optimized a previously published procedure capable of extracting transesterifiable lipids from wet algal biomass. This optimization resulted in the extraction of 77% of the total transesterifiable lipids, while reducing the amount of materials and temperature required in the procedure. In addition, characterization of side streams generated demonstrated that: (1) the C/N ratio of the residual biomass or lipid extracted (LE) biomass increased to 54.6 versus 10.1 for the original biomass, (2) the aqueous phase generated contains nitrogen, phosphorous, and carbon, and (3) the solid precipitate phase was composed of up to 11.2 wt% nitrogen (70% protein). The ability to isolate algal lipids and the possibility of utilizing generated side streams as products and/or feedstock material for downstream processes helps promote the algal biorefinery concept.